TLR4, but Neither Dectin-1 nor Dectin-2, Participates in the Mollusk Hemocyanin-Induced Proinflammatory Effects in Antigen-Presenting Cells From Mammals - Jiménez, José M.; Salazar, Michelle L.; Arancibia, Sergio; Villar, Javiera; Salazar, Fabián; Brown, Gordon D.; Lavelle, Ed C.; Martínez-Pomares, Luisa; Ortiz-Quintero, Jafet; Lavandero, Sergio; Manubens, Augusto; Becker, María Inés (Frontiers in Immunology, 2019)
Mollusk hemocyanins have biomedical uses as carriers/adjuvants and nonspecific immunostimulants with beneficial clinical outcomes by triggering the production of proinflammatory cytokines in antigen-presenting cells (APCs) and driving immune responses toward type 1 T helper (Th1) polarization. Significant structural features of hemocyanins as a model antigen are their glycosylation patterns. Indeed, hemocyanins have a multivalent nature as highly mannosylated antigens. We have previously shown that hemocyanins are internalized by APCs through receptor-mediated endocytosis with proteins that contain C type lectin domains, such as mannose receptor (MR). However, the contribution of other innate immune receptors to the proinflammatory signaling pathway triggered by hemocyanins is unknown. Thus, we studied the roles of Dectin-1, Dectin-2 and Toll like receptor 4 (TLR4) in the hemocyanin activation of murine APCs, both in dendritic cells (DCs) and macrophages, using hemocyanins from Megathura crenulata (KLH), Concholepas concholepas (CCH) and Fissurella latimarginata (FLH). The results showed that these hemocyanins bound to chimeric Dectin-1 and Dectin-2 receptors in vitro; which significantly decreased when the glycoproteins were deglycosylated. However, hemocyanin-induced proinflammatory effects in APCs from Dectin-1 knock-out (KO) and Dectin-2 KO mice were independent of both receptors. Moreover, when wild-type APCs were cultured in the presence of hemocyanins, phosphorylation of Syk kinase was not detected. We further showed that KLH and FLH induced ERK1/2 phosphorylation, a key event involved in the TLR signaling pathway. We confirmed a glycan-dependent binding of hemocyanins to chimeric TLR4 in vitro. Moreover, DCs from mice deficient for MyD88-adapter-like (Mal), a downstream adapter molecule of TLR4, were partially activated by FLH, suggesting a role of the TLR pathway in hemocyanin recognition to activate APCs. The participation of TLR4 was confirmed through a decrease in IL-12p40 and IL-6 secretion induced by FLH when a TLR4 blocking antibody was used; a reduction was also observed in DCs from C3H/HeJ mice, a mouse strain with a nonfunctional mutation for this receptor. Moreover, IL-6 secretion induced by FLH was abolished in macrophages deficient for TLR4. Our data showed the involvement of TLR4 in the hemocyanin-mediated proinflammatory response in APCs, which could cooperate with MR in innate immune recognition of these glycoproteins.